Early versus late transition metals. Electronic structure of nido-2-CpMLnB4H8, CpMLn = CpTaCl2, CpWH3 and CpCo - Weller, A; Aldridge, S; Fehlner, T (1999)
The mono-metal analog of B5H9, 2-CpCoB4H8, is used as a benchmark for the interpretation of molecular orbital calculations on 2-CpWH3B4H8 and 2-CpTaCl2B4H8, all of which have square pyramidal cluster cores. The latter two molecules are shown to obey the prescription of the cluster electron counting rules for a nido, five atom cluster. On the other hand, although both 2-CpCoB4H8 and 2-CpWH3B4H8 possess metals that obey the 18 electron rule, the metal atom in 2-CpTaCl2B4H8 must be viewed as a 16 electron center. Further, it is shown that the asymmetric ligand arrangements about the metal centers in 2-CpWH3B4H8 and 2-CpTaCl2B4H8 are required in order to satisfy the demands of cluster bonding. Finally, the magnitude of the barrier for rotation of the CpMLn fragment in the same two compounds relative to the borane core depends on the number of ligands, n, via the magnitude of the splitting of the metal frontier orbitals. © 1999 Elsevier Science S.A.